Quasi-zero rigidity condition for static force characteristic of parallelogram mechanism for seat vibration protection system - M. S. Korytov; I. E. Kashapova; V. S. Shcherbakov (Вестник СибАДИ)
Introduction. Reducing vibration effects on machine operators is an urgent task; it allows to minimize the impact of vibrations on health, increase efficiency and attention. Accuracy and productivity can be improved. The problem of vibration protection is relevant for all types of machines, the working bodies of which interact with the soil and road surface. One of the impact reduction directions, along with vibration protection of cabs, is the development of vibration protection systems for operator seats. It is promising to use the effect of quasi-zero rigidity, which makes it possible to effectively damp low-frequency oscillations. For the proposed design based on a parallelogram mechanism, it is necessary to determine the condition for the horizontalness of the middle section of the static power characteristic.Materials and Methods. For the developed design scheme, using well-known power static and geometric relationships, novel analytical relationships between the parameters of the initial data and the vertical lifting force of the mechanism were derived. The initial parameters include the linear dimensions of the mechanism, the size of the quasi-zero rigidity zone, the weight of the chair with the operator, and the spring stiffness. When deriving analytical dependencies, the coordinates of the points of the mechanism moving and stationary relative to their own base were used.Results. The use of the developed analytical dependencies allows, for the given parameters of the initial data, to build a static power characteristic of the mechanism. The middle section of the characteristic is close to horizontal, but in general it is not horizontal. As an example, a static characteristic is given for a set of initial data values, the middle part of which is not horizontal. Equating the values of the vertical force of the mechanism at the left and right boundary points of the middle part of the characteristic made it possible to determine analytical dependences for ensuring quasi-zero rigidity.Discussion and conclusions. The obtained analytical expressions for ensuring the horizontalness of the middle section of the static power characteristic were verified. Applying the derived conditions decreases the number of parameters in the original data by one. An increase in the two dimensional parameters of the mechanism significantly reduces the required rigidity of the mechanism spring, which reduces the metal consumption.